1995
DOI: 10.1148/radiology.197.3.7480726
|View full text |Cite
|
Sign up to set email alerts
|

Change in endometrial thickness in postmenopausal women undergoing hormone replacement therapy.

Abstract: Women using sequential hormones show greater endometrial thickness than that in controls and show the most variation in measurements. They should undergo US either early or late in the hormone cycle to evaluate the endometrium at its thinnest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…Levine and coworkers reported a patient on CCT with an ET of 8 mm who was found to have atrophy on biopsy. 4 Four women receiving Kliofem with ET values ranging from 9 to 15 mm showed either pseudodecidual change or atrophy with polyps or a fibroid. 3 Of further note is the report that the SERM agent idoxifene induced an ET of 5 mm or greater in 16% of subjects over the course of 12 weeks, but histologic features were unremarkable.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Levine and coworkers reported a patient on CCT with an ET of 8 mm who was found to have atrophy on biopsy. 4 Four women receiving Kliofem with ET values ranging from 9 to 15 mm showed either pseudodecidual change or atrophy with polyps or a fibroid. 3 Of further note is the report that the SERM agent idoxifene induced an ET of 5 mm or greater in 16% of subjects over the course of 12 weeks, but histologic features were unremarkable.…”
Section: Discussionmentioning
confidence: 93%
“…The endometrium does not appear to change with time on treatment with opposed therapy. Histologically the endometrium did not show a tendency toward hyperplasia with time in younger women taking 2 mg 17 β-estradiol plus 1 mg norethindrone (norethisterone), 3 although a suggestion of increasing thickness with time was noted with sequential therapy 4 ; however, the effect of low dose CCT, e.g., 300 µg conjugated equine estrogens or 25 µg Estraderm patch (Ciba Consumer Pharmaceuticals, Woodbridge, NJ), on ET over the long term remains to be studied. The effect of age as a factor in determining endometrial response has been investigated infrequently, but one study of ET found no relation between ET and either weight or age.…”
Section: Ilona Wanda Chantler Mb Chb Michael William John Davie Mmentioning
confidence: 96%
See 1 more Smart Citation
“…This measurement represented two layers of the endometrium (17) . In the presence of fluid in the endometrial canal, the two half thickness endometrial measurements were added together (18) .…”
Section: Methodsmentioning
confidence: 99%
“…Endometrial thickening is a non specific finding which is seen with secretory endometrium, estrogen therapy, early pregnancy, endometrial hyperplasia, polyps and endometrial carcinoma. Sub endometrial pathologic condition such as submucosal myoma and adenomyosis may also manifest as apparent endometrial thickening 3 . Abdominal or transvaginal sonography can identify thickened endometrium but unable to differentiate between potential etiologies of thickened endometrium like polyps, endometrial hyperplasia, submucous fibroid or endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%